A temporal model of team mentoring: a grounded theory approach. (2nd November 2021) - Xie, Lei; Kogut, Ashlynn; Beyerlein, Michael; Boehm, Rodney
ABSTRACT : This grounded theory research examined the actions mentors take to help student teams. We interviewed nine mentors from an engineering competition using semi-structured interviews. We studied the interactions between mentors and student teams and identified nine mentoring actions: initiating the relationship, strategies to develop thinking, active involvement in the design process, keeping the team on track, empathising with the team, monitoring team dynamics, offering appropriate amount of support, providing information, and giving career advice. These nine actions can be mapped into a temporal model of team mentoring with two dimensions – the teamwork process dimension comprises mentoring actions that target team relationship building, and the teamwork foundation dimension consists of mentoring actions that focus on the product or design, the outcome of the team interactions. This Temporal Model of Team Mentoring (TMTM) advances the theoretical conceptions of team mentoring and can be used as a guide for team mentor training.